Phosphorylation of T107 by CamKII[delta] regulates the detoxification efficiency and proteomic integrity of glyoxalase 1 - Morgenstern, Jakob; Katz, Sylvia; Krebs-Haupenthal, Jutta; Chen, Jessy; Saadatmand, Ali R.; Garcia Cortizo, Fabiola; Zemva, Johanna; Campos Campos, Marta; Teleman, Aurelio A.; Backs, Johannes; Nawroth, Peter Paul; Fleming, Thomas (Cell reports, 2020)
The glyoxalase system is a highly conserved and ubiquitously expressed enzyme system, which is responsible for the detoxification of methylglyoxal (MG), a spontaneous by-product of energy metabolism. This study is able to show that a phosphorylation of threonine-107 (T107) in the (rate-limiting) Glyoxalase 1 (Glo1) protein, mediated by Ca2+/calmodulin-dependent kinase II delta (CamKIIδ), is associated with elevated catalytic efficiency of Glo1 (lower KM; higher Vmax). Additionally, we observe proteasomal degradation of non-phosphorylated Glo1 via ubiquitination does occur more rapidly as compared with native Glo1. The absence of CamKIIδ is associated with poor detoxification capacity and decreased protein content of Glo1 in a murine CamKIIδ knockout model. Therefore, phosphorylation of T107 in the Glo1 protein by CamKIIδ is a quick and precise mechanism regulating Glo1 activity, which is experimentally linked to an altered Glo1 status in cancer, diabetes, and during aging.